STUDI KOMPARATIF PERILAKU STRUKTUR GEDUNG BETON BERTULANG DENGAN VARIASI GEOMETRI KOLOM PERSEGI DAN KOLOM BULAT - Sutama, Adji; Septriansyah, Verinazul; Angraini, Dina Dwi (Universitas Muhammadiyah Palembang, 2024)
This research aims to analyze the comparative structural behavior of reinforced concrete buildings using variations in square and circular column geometries. The research object is a 6-story educational building with dimensions of 35.1 x 23.4 meters and a total height of 24.2 meters. The analysis was conducted using ETABS v18 software by varying square column dimensions (55/55 cm, 50/50 cm, 45/45 cm) and circular columns (diameters of 62 cm, 56 cm, 50 cm). The parameters examined include internal forces, section capacity, and structural drift. Research results indicate that the difference in internal forces between the two column types is relatively small (1-2%). Circular columns demonstrate higher capacity in resisting axial loads (5098.01-7609.09 kN) and moments (295-520 kNm) compared to square columns. Although circular columns show slightly larger drift values, both column types meet the established drift limit requirements with safe margins. This research concludes that both column geometries demonstrate good structural performance and can be used interchangeably in structural design, with circular columns having advantages in section capacity but accompanied by slightly larger drift values.